Journal of Cellular Signaling 2022
DOI: 10.33696/signaling.3.068
|View full text |Cite
|
Sign up to set email alerts
|

c-JUN n-Terminal Kinase (JNK) Signaling in Autosomal Dominant Polycystic Kidney Disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a common inherited disorder characterized by slow-growing, fluid-filled cysts in both kidneys. Liver and pancreatic cysts as well as cardiac and vascular abnormalities variably occur [1,2]. ADPKD symptoms include hypertension, kidney pain, hematuria, cyst infection, and urinary tract infections [1]. Over time, deteriorating kidney function leads to end stage renal disease (ESRD). While most ADPKD patients progress to ESRD by age 70, many reach it at young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 179 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…Polycystic kidney disease (PKD) is a degenerative kidney disease wherein the renal tubules are filled with multiple fluid-filled cysts [198]. Autosomal dominant polycystic kidney disease (ADPKD) is one kind of PKD.…”
Section: Autosomal Dominant Polycystic Kidney Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Polycystic kidney disease (PKD) is a degenerative kidney disease wherein the renal tubules are filled with multiple fluid-filled cysts [198]. Autosomal dominant polycystic kidney disease (ADPKD) is one kind of PKD.…”
Section: Autosomal Dominant Polycystic Kidney Diseasementioning
confidence: 99%
“…ADPKD has been shown to be caused by mutations of the polycystin-1 (Pkd1) and Pkd2 genes. Smith et al recently found that the JNK pathway is involved in ADPKD as inhibition of JNK activity reduces cyst growth [198].…”
Section: Autosomal Dominant Polycystic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation